Research on the grinding performance of high pressure sintering SiCp/Al matrix composites - Chen, Zhiru (Array, 2018)
The two-dimensional vertical grinding test equipment was used to grind SiCp/Al composites which were prepared by high pressure sintering method. The SEM observation of grinding morphology showed that grinding damage can be prevented by SiC particles reinforcement, 60% volume fraction of SiC particles of SiCp/Al composite can hinder grinding depth and grinding performance was improved with the sintering pressure and temperature increasing. In addition, some scratches and exfoliated pits of SiC particles were observed on the surface of 60% volume SiCp/Al composite as the increase of grinding grain, while the depth of these scratches was shallower, there was no large area exfoliated pits of SiC reinforcements.